2013
DOI: 10.3844/ijrnsp.2013.14.21
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Self-Management Support Program on Diabetic Foot Care Behaviors

Abstract: Diabetic Foot Care Behaviors (DFCB) is the fundamental component of diabetic foot complications prevention. Many diabetic patients, however, did not perform foot care properly. Furthermore, SelfManagement (SM) support program was noted as effective approach improving diabetes patients' behaviors. Unfortunately, there have been no studies published applied this approach to improve DFCB in Indonesia. This study aimed to determine the effectiveness of a self-management support program in improving DFCB in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…; Sae‐Sia et al. ). Predominately, the literature showed that assessing diabetic foot ulcers was undertaken by either a physician or a nurse.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…; Sae‐Sia et al. ). Predominately, the literature showed that assessing diabetic foot ulcers was undertaken by either a physician or a nurse.…”
Section: Resultsmentioning
confidence: 98%
“…Other HCPs roles were identified in the literature; however, these roles still need development in the areas of providing patient information and providing diabetes care, for example diabetes foot care (Sae‐Sia et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Educational materials will increase understanding and stimulate the enthusiasm of patients and families in following the material presentation (7). Also previous research reported that support for self-management would improve self-care behavior (14). It can be analyzed that family support for self-management with the help of good educational materials will certainly produce knowledge effectiveness in patients.…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] Various other studies also showed improvement in patient knowledge and foot care behavior with educational intervention. [ 12 13 14 15 ]…”
Section: Discussionmentioning
confidence: 99%